Arquivo Público do Estado do Pará: um olhar sobre o perfil dos usuários (2015-2018) - MELO, Luziane da Costa (2021)
This study aimed to identify the user profile of the Public Archive of the State of Pará in the period from 2015 to 2018. The methodological tools used were based in the bibliographic research, mainly books and academic articles that deal with the subject in question and in the documentary research that enabled the collection of quantitative data, obtained in the files of consultation of the Public Archive of the State of the Pará. Such results shown through graphs subsidized the qualitative descriptive analysis quantitative of the present research based on the answers obtained, through the collected data, it was observed that among the users attending the APEP, within the temporal cut, the Paraenses, from the academic milieu stand out; especially the History and Pedagogy courses in search of documentation to subsidize their undergraduate and graduate research.